Persamaan Fungsi Linear dalam Analisa Penjualan 2020 pada UMKM Kuliner RIN SWEET CAKES & COOKIES, Loa Janan Samarinda - Achmad Rudzali; Diyah Permana (Jurnal EKSIS, 2022)
A business that lasts a long time without realizing it may not actually be profitable, but it is still going on. From this statement, the BEP for Rin Sweet Cakes and Cookies culinary was began. In addition, fluctuations in material prices and other costs often change every month. The analysis was carried out through linear equation graph by utilizing the sales and cost equations that occurred throughout 2020. So that the BEP value, margin of safety and future sales plans are produced. The results of the analysis stated that the production volume during BEP was around 2,594 pcs consisting of muffins, roti gembong and lapis legit. The margin of safety is 14.31%. The average operating profit obtained in 2020 is Rp. 5,662,046,- by bearing the loss for muffin products Rp.666.751,- and lapis legit Rp. 1.452.859,-. Based on sales data for 2020, the lapis legit will be a possible product to be made in future sales business plans.